Kummels, Ingrid y Gisela Cánepa. Fotografía en América Latina: imágenes e identidades a través del tiempo y el espacio. Lima: Instituto de Estudios Peruanos, 2018. - Biffi, Valeria (Pontificia Universidad Católica del Perú. Fondo Editorial, 2018)
This volume brings together research on contemporary uses of historical photographs from Brazil, Colombia, Mexico and Peru, conducted between 1880 and 1980. Case studies discuss how photos of the past, in the light of contemporary times and the challenges of the digital age, are answered, recontextualized and resignified. The volume poses new challenges for visual anthropology, highlighting the contrast between fluency, sense of belonging and affection, to explore the contemporary significance of historical photography in processes of constitution of memory, ethnographic imagination and identity in Latin America.

Este volumen reúne investigaciones sobre usos contemporáneos de fotografías históricas de Brasil, Colombia, México y Perú, realizadas entre 1880 y 1980. Los estudios de caso discuten de qué manera fotos del pasado, a la luz de la contemporaneidad y los desafíos de la era digital, son contestadas, recontextualizadas y resignificadas. El volumen plantea nuevos desafíos para la antropología visual, destacando el contraste entre fluidez, sentido de pertenencia y afecto para explorar la significación contemporánea de la fotografía histórica en procesos de constitución de memoria, imaginación etnográfica e identidad en América Latina.
Kummels, Ingrid and Gisela Cánepa. Photography in Latin America: images and identities through time and space. Lima: Instituto de Estudios Peruanos, 2018.
Keywords: Fotografía; Historia; América Latina; Memoria; Imaginación etnográfica; Identidad; https://purl.org/pe-repo/ocde/ford#5.04.03